Prevalence and risk factors associated with non-communicable diseases among employees in a university setting: A cross-sectional study - Annie Kuruvilla; Sonal Mishra; Koustav Ghosh (Elsevier, 2023)
Background: Globally, around 41 million people die due to non-communicable diseases (NCDs) which accounts for more than 75% of global deaths. The major NCDs, namely, Cardiovascular diseases, Cancers, Respiratory diseases and Diabetes accounts for 80% of deaths in the world. This is one of the major public health concerns in low and middle-income countries like India. The present study aims to study the prevalence and risk factors associated with Non-Communicable Diseases among employees in a university setting in Gujarat. Methods: Primary data was collected through a structural questionnaire with the guidelines given by WHO STEP-wise approach to NCDs. There was total 1025 participants in the study. Bivariate and logistics regression were used to show the prevalence and the influence of risk factors of NCDs with the help of STATA 14 software. Results: Prevalence of NCDs among the university employees was 10.15%. The prevalence of diabetes (DM), cardio vascular diseases (CVDs) and hypertension were 7.2%, 3.2% and 17% respectively. Having family history of chronic diseases (OR: 2.17; 95% CI:1.39-3.41) and >50 years of age (OR:3.47; 95% CI:1.19-10.14) were 2.17 and 3.47 times at higher risk of NCDs. Moreover obesity (OR: 8.34; 95% CI: 1.12-9.42), unhealthy waist-hip-ratio and hypertension (OR: 1.85; 95% CI:1.15-2.96) increase the risk of such diseases. Conclusion: The study recommends to focus on employees who have history of chronic diseases in their families and encourage people and households to reduce the risk of NCDs through changes in lifestyle, namely physical activity and improvement in substance abuse behaviour.